Measurements of inclusive J/ψ production at midrapidity and forward rapidity in Pb-Pb collisions at √𝑠NN = 5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kroesen, Martin; Nath, Abhishek; et al. (Physics letters, 2024)
The measurements of the inclusive J∕𝜓 yield at midrapidity (|𝑦| < 0.9) and forward rapidity (2.5 < 𝑦 < 4) in Pb–Pb collisions at √𝑠NN = 5.02 TeV with the ALICE detector at the LHC are reported. The inclusive J∕𝜓 production yields and nuclear modification factors, 𝑅AA, are measured as a function of the collision centrality, J∕𝜓 transverse momentum (𝑝T), and rapidity. The J∕𝜓 average transverse momentum and squared transverse momentum (⟨𝑝T⟩ and ⟨𝑝2 T⟩) are evaluated as a function of the centrality at midrapidity. Compared to the previous ALICE publications, here the entire Pb–Pb collisions dataset collected during the LHC Run 2 is used, which improves the precision of the measurements and extends the 𝑝T coverage. The 𝑝T-integrated 𝑅AA shows a hint of an increasing trend towards unity from semicentral to central collisions at midrapidity, while it is flat at forward rapidity. The 𝑝T-differential 𝑅AA shows a strong suppression at high 𝑝T with less suppression at low 𝑝T where it reaches a larger value at midrapidity compared to forward rapidity. The ratio of the 𝑝T-integrated yields of J∕𝜓 to those of D0 mesons is reported for the first time for the central and semicentral event classes at midrapidity. Model calculations implementing charmonium production via the coalescence of charm quarks and antiquarks during the fireball evolution (transport models) or in a statistical approach with thermal weights are in good agreement with the data at low 𝑝T. At higher 𝑝T, the data are well described by transport models and a model based on energy loss in the strongly-interacting medium produced in nuclear collisions at the LHC.
Online verfügbar 12 January 2024, Version des Artikels 24 January 2024
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, J. Crkovská, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, M. Völkl, B. Windelband, A. Yuncu, F. Zanone [und viele weitere]
Gesehen am 19.07.2024